The Leishmania Parasitophorous Vacuole Membrane at the Parasite-Host Interface - Young, Jeffrey (Yale J Biol Med, 2019)
The Leishmania parasitophorous vacuole membrane (LPVM) sits at the interface of the parasite and its host. Evidence shows that molecules from the endocytic pathway as well as molecules from the secretory pathway are localized in the LPV and displayed on LPVM. In the review, we discuss our current understanding of the composition of the LPVM.